(untitled) (Italian Journal of Public Health, 2004)
The Regional Health Observatories (RHOs) were created in France in the 1980’s. They exist in each of the 26 regions. Their principal mission is to assist in the decision making process by the undertaking of in-depth analyses of the populations’ health status. To achieve this aim they catalogue and validate existing data, promote surveys when there is a lack of information, disseminate the collected information and conduct evaluations of public health interventions. Around 400 people work in the observatories (241 full-time equivalents) with various expertise including public health doctors, statisticians, sociologists, demographers, geographers, economists etc. More than 40% of the budget of the RHOs comes from the government while 21% comes from the local executive. RHOs work with all the regional and local institutions concerned with health programs and policies. The main role of the RHOs in this context is to identify the health needs, to describe health related behaviours and to describe the utilisation of the health care system. The analysis of the different kinds of work conducted shows the great diversity of the subjects treated by the observatories. The creation in 1989 of the “Fédération Nationale des Observatoires Régionaux de Santé” (FNORS) strengthened the links within the RHOs. Its role is to represent the RHO network and to facilitate the harmonisation of the inter-RHOs projects. Recently, the FNORS increase its position to represent RHOs at the European level by taking part in EU projects and to promote the creation of a European network of regional health observatories.